The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1590/s0124-00642007000400008
|View full text |Cite
|
Sign up to set email alerts
|

Validación de la Escala de Somnolencia de Epworth

Abstract: ESS-VC compared well with the original version. It is well adapted to urban life conditions in the Colombian adult population, reliable, valid and sensitive to reported changes. It had clinically and statistically significant correlation with polysomnography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
28

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 11 publications
1
24
0
28
Order By: Relevance
“…For the 135 individuals assessed in the present study, the scores obtained on the ESS-BR showed internal consistency similar to that of translations validated elsewhere, (24)(25)(26)(27)(28) despite the cultural and language differences among the populations analyzed. Comparing the ESS-BR scores obtained in the present study with those obtained in studies applying the original ESS, we found the scores to be similar for the control and OSAHS groups.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…For the 135 individuals assessed in the present study, the scores obtained on the ESS-BR showed internal consistency similar to that of translations validated elsewhere, (24)(25)(26)(27)(28) despite the cultural and language differences among the populations analyzed. Comparing the ESS-BR scores obtained in the present study with those obtained in studies applying the original ESS, we found the scores to be similar for the control and OSAHS groups.…”
Section: Discussionsupporting
confidence: 77%
“…The relationship between snoring and EDS has previously been suggested. (26) In the present study, this difference might be attributable due to a selection bias, since most of the patients in the primary snoring group were referred for polysomnography due to clinical suspicion of OSAHS. In addition, some of these patients might have had increased airway resistance.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The ESS and BQ were chosen due to their frequent use in the obstetric OSA literature, and possibly the population (12)(13)(14)(15)(16). The ESS has been validated in the Spanish language and in Hispanic populations (17)(18)(19). At study initiation, neither questionnaire had been validated in a gravid population; a separate analysis of this study sought to assess the validity of these two questionnaires in pregnancy.…”
Section: Methodsmentioning
confidence: 99%
“…This scale has been used in different studies of genetics of circadian phenotypes [14-16]. We used the validated version in Spanish of the ESS [11], that has also been used before in a Colombian sample [17]. The internal consistency (Cronbach’s alpha) in this sample was 0.716.…”
Section: Materials and Methodologymentioning
confidence: 99%